Deliberative Dialogue as a Viable Instructional Method for Civic Learning Outcomes - Adesegun Olayide Odutayo (Studies in Learning and Teaching, 2023)
Civic education aids students in acquiring the skills necessary to create a democratic society. The effectiveness of deliberative dialogue as an instructional method on civic learning outcomes was investigated in this study. A quasi-experimental design was used for the investigation. In Ilorin, two secondary schools were randomly chosen and split into experimental and control groups. The sample for this study consisted of 73 students (control group: 38; experimental group: 35). An eight-week study was conducted. The Civic Learning Test (CLT), a fifty-item multiple-choice test with sufficient validation, served as the instrument for data collection. The Spearman-Brown Prophesy Formula yielded a reliability index of 0.78 using SPSS statistics (23.0). Mean and standard deviation were used to respond to research question 1, and ANCOVA was used to test the two research hypotheses at a 0.05 significance level. The results showed that students participating in deliberative dialogue had significantly better civic learning outcomes. Additionally, there is no discernible gender difference in the civic learning outcomes of students who participated in deliberative dialogue. It was recommended that the Government, through NERDC, include deliberative dialogue as a legitimate instructional method in the curriculum.